Pressure Injury Documentation Practices in the Department of Veteran Affairs: A Quality Improvement Project. Issue 1 (January 2019) - Chavez, Margeaux A.; Duffy, Allyson; Rugs, Deborah; Cowan, Linda; Davis, Avaretta; Morgan, Storm; Powell-Cope, Gail
Abstract : Evidence suggests that inaccurate and incomplete pressure injury (PI) documentation threatens the validity of treatment and undermines policy and quality improvement. This quality improvement project sought to identify barriers and facilitators when conducting and documenting the daily comprehensive skin assessment in 31 Department of Veterans Affairs (VA) facilities. Evaluators in this 1-year, cross-sectional quality improvement project, using a qualitative approach, interviewed nurses of medical-surgical and critical care units. Participants (N = 62) from 12 high reassessment units (HRUs) and 13 low reassessment units (LRUs) were interviewed using telephone focus groups. Staff from HRUs reported 9 activities that ensured consistency in clinical practices, in validating data, and in correcting inaccuracies. The LRU staff tended to report performing only 2 of the 9 activities. The main barriers to accurate documentation were lack of knowledge, poor templates, and staffing issues such as understaffing and turnover, and main facilitators were an internal data validation process and a documentation template to local practices. Findings from this project led to increased VA leadership engagement, development of 3 innovative, award-winning VA mobile PI prevention and management applications, updated policies and directives on PI prevention, and upgrading of the national VA HAPI workgroup to an advisory committee and improved collaboration between the PI advisory committee and nursing informatics.